2020
DOI: 10.5194/egusphere-egu2020-3020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biotic and abiotic controls on carbon storage in aggregates from grassland soils in the Northern Limestone Alps of Germany

Abstract: <p>Alpine and pre-alpine grassland soils in Bavaria provide important ecosystem services and are hotspots for soil organic carbon (SOC) storage.  However, information on the underlying factors that control SOC stabilization via soil aggregation is limited. In three grassland soils with the same parent material but at different elevation (Fendt: 600 m.a.s.l, Graswang: 860 m a.s.l and Esterberg: 1,260 m a.s.l), we studied the soil aggregate distribution and associated SOC according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, several studies have shown that agricultural management activities can indeed generate changes in the dynamics of SIC (3)(4)(5). These alterations can be reflected in the amounts, mineralogy and morphology of carbonates of carbonates in superficial soil layers in relatively short time lapses (6)(7)(8)(9). This is so because agricultural management normally implies changes in the chemistry of the soil solution through for example fertilization, incorporation of amendments such as lime, and irrigation with water of different quality (3,6,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that agricultural management activities can indeed generate changes in the dynamics of SIC (3)(4)(5). These alterations can be reflected in the amounts, mineralogy and morphology of carbonates of carbonates in superficial soil layers in relatively short time lapses (6)(7)(8)(9). This is so because agricultural management normally implies changes in the chemistry of the soil solution through for example fertilization, incorporation of amendments such as lime, and irrigation with water of different quality (3,6,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%